1975
DOI: 10.1136/jramc-121-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Smoking: The Changing Habits of Male Adolescents a Comparison of Three Generations of Young Soldiers

Abstract: The smoking habits of three generations of junior entrants to the Army, aged 15 to. 18 years, have been examined by questionnaires in 1959, 1966 and 1971. An assessment has been made from these three comparable populations of adolescent males of changes in smoking habits over the 12-year period in question. The results indicate a slight increase in the proportion who have never tried smoking. Of those who have smoked, the age of starting feU between 1959 and 1966 but remained almost constant thereafter. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Successive cohorts of young soldiers were surveyed by age group in 1959, 1966 and 1971. Although there was only a 3% fall in the prevalence of current smoking in 15-year old soldiers between 1959 and 1971, the prevalence fell by 9% in 16-year old soldiers, 11% in 17-year old soldiers and 16% in 18-year old soldiers over the same period 21. It may be inferred that while the smoking habits of the newly joined 15-year old soldiers largely reflected those of the general population background from which they were drawn, exposure to health education in service had a progressively beneficial impact throughout the 3 years of junior service.…”
Section: Discussionmentioning
confidence: 93%
“…Successive cohorts of young soldiers were surveyed by age group in 1959, 1966 and 1971. Although there was only a 3% fall in the prevalence of current smoking in 15-year old soldiers between 1959 and 1971, the prevalence fell by 9% in 16-year old soldiers, 11% in 17-year old soldiers and 16% in 18-year old soldiers over the same period 21. It may be inferred that while the smoking habits of the newly joined 15-year old soldiers largely reflected those of the general population background from which they were drawn, exposure to health education in service had a progressively beneficial impact throughout the 3 years of junior service.…”
Section: Discussionmentioning
confidence: 93%
“…No data are available on the prevalence of smoking in the Pay Corps spec ifically, but, in the Army as a whole, the habit has been common. In a survey of 15-to 18-year -old entrants to the Army in 1959, 76% had smoked during the previous four weeks and 53% smoked at least 20 cigarettes per week (9). Smoking habits may also have accounted for the referen ts' increased mortal ity from respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is the largest preventable cause of death in the United Kingdom (1,2), but a recent survey has shown that 50tlfo of young soldiers still smoke (3), a figure which has fallen little in the last 20 years (4,5), against the national trend (6). Studies have shown that soldiers have an increased risk of premature ischaemic heart disease when compared with civilian contemporaries of similar socioeconomic status (7,8): the only differing risk factor is that soldiers smoke more heavily (9).…”
Section: Introductionmentioning
confidence: 99%